234 Outcomes of Periprosthetic Femoral Fractures Between 2011–2021: An Observational Study. (28th February 2022) - Singh, H.; Bista, A.; Baggott, J.; Unnithan, A.; Sobti, A.; Farook, M.; Jacob, J.; Khaleel, A.; Elliot, D.
Abstract: Background: Periprosthetic femoral fractures (PPFF) present a significant burden on the health services due to an increase in the ageing population and the number of hip and knee arthroplasties performed. This study observed how this burden changed between 2011 and 2021 and the outcomes for these patients undergoing an operation. Method: Ten-year retrospective observational study assessing the variance depending on the fracture/operation, ASA scores, time to operation, length of stay and mortality. Results: From January 2011 to March 2021, we identified 209 operations for femur periprosthetic fractures. The mean age was 83 with a female preponderance of 76%. There was a significant change in the ASA scores of the patients, with the proportion of ASA 3 or more increasing from 43% (2011–2016) to 73% (2017–2021), and ASA 4 or greater increasing from 10% to 17% respectively. There were 68 periprosthetic hip arthroplasty fracture fixations, 81 periprosthetic hip arthroplasty fracture revisions, 45 periprosthetic total knee replacements, and 15 inter-prosthetic fractures. One year mortality rates were 24.6%, 6.7%, 16.3% and 13.3% respectively. The average times to operation were 2.5 days, 4.5 days, 2.1 days, and 1.7 days respectively. The average lengths of stay were 20.8 days, 19.8 days, 12.1 days, and 13.1 days respectively. Conclusions: PPFF carry a significant mortality risk and ASA scores have increased. Mortality rates were better in the periprosthetic hip arthroplasty patients who had revisions rather than fixations (representing different cohort). one year mortality figures were comparable to similar studies in Ireland and USA.